Surface protective film
By using a laminated structure of a width-direction uniaxial stretched polyester substrate and an acrylic polymer adhesive layer in the polyester surface protective film, the problem of difficulty in taking into account both hand tearability and reprocessability is achieved. Efficient peeling and re-fitting on polyester-based surface protective film.
Patent Information
- Application Number
- CN202411148486.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-07-05
- Filing Date
- 2017-07-04
- Publication Date
- 2024-12-17
AI Technical Summary
The existing polyester-based surface protective film is difficult to take into account good hand tear and high reworkability during the manufacturing process, which leads to prone to cracking during reprocessing and unable to fit again.
A laminated structure consisting of a transparent substrate and an adhesive layer is a width-direction uniaxially stretched polyester substrate, and the adhesive layer contains acrylic polymer. Elmendorf tear strength is on the substrate. The width direction is less than 0.5N and the length direction is more than 1N to ensure hand tear and adhesion.
It achieves good hand tear and high reworkability on polyester substrates, avoids cracking problems during peeling and re-stitching, and is suitable for surface protection of optical components.
Smart Images

Figure CN119144243A_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application with application date of July 4, 2017 and application number 201710537175.X. Technical Field
[0002] The present invention relates to a light-transmitting surface protective film. Background Art
[0003] In recent years, surface protection films with high transparency have been used in various technical fields. For example, in the technical field of flat panel displays (FPDs), various optical components assembled in FPDs are sometimes attached with surface protection films on the surface of the components for the purpose of surface protection during the manufacturing process, inspection process, transportation process, etc. Such surface protection films are described in the following patent documents 1 to 3, for example.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2012-17399
[0007] Patent Document 2: Japanese Patent Application Publication No. 2015-157964
[0008] Patent Document 3: Japanese Patent Application Publication No. 2016-74899 Summary of the invention
[0009] Problems to be solved by the invention
[0010] As the substrate of the surface protection film, a polyester substrate is sometimes used because of its excellent heat resistance, transparency, dimensional stability and other characteristics. For a light-transmitting polyester substrate such as a PET film used as a surface protection film for optical parts, it is known that in many cases, the raw resin material is extruded into a film by a T-die method in the manufacturing process, and then subjected to a biaxial stretching treatment including stretching in the flow direction or length direction (MD) of the film and stretching in the width direction (TD).
[0011] In addition, the surface protection film may be required to have good hand-tearability from the viewpoint of work efficiency and the like.
[0012] The present invention has been conceived based on the above circumstances, and an object of the present invention is to provide a surface protection film which is suitable for having a polyester-based substrate and achieving both good hand-tearability and high reworkability.
[0013] Means used to solve problems
[0014] The surface protection film provided according to the present invention has a laminated structure including a transparent substrate and an adhesive layer. The transparent substrate is a polyester substrate uniaxially stretched in the width direction of the substrate and has a thickness of 75 μm or more. A polyester substrate refers to a substrate such as a film or sheet containing a polyester resin in the largest weight proportion in the constituent materials. A polyester substrate uniaxially stretched in the width direction of the substrate refers to a polyester substrate that has been subjected to uniaxial stretching treatment, for example, in a width direction (TD) orthogonal to the flow direction or length direction (MD) of a film-shaped extruded body after extrusion molding of the raw resin material in the manufacturing process of the polyester substrate. The adhesive layer, for example, contains at least one selected from the group consisting of acrylic adhesives, polyurethane adhesives, polysiloxane adhesives and rubber adhesives. In the present surface protection film, the Elmendorf tear strength in the width direction of the substrate is less than 0.5N, and the Elmendorf tear strength in the length direction of the substrate is more than 1N.
[0015] As described above, the transparent substrate of the present surface protection film is a polyester substrate. Such a configuration is suitable for the surface protection film substrate, and further the present surface protection film, to have various properties that polyester substrates tend to exhibit, such as heat resistance, transparency, and dimensional stability.
[0016] In addition, as described above, the transparent substrate of the present surface protection film is a uniaxially stretched polyester substrate having a thickness of 75 μm or more in the width direction. The tear strength of the surface protection film, such as the Elmendorf tear strength, is strongly controlled by the mechanical properties of the substrate, and such a configuration is suitable for achieving the above-mentioned configuration in which the Elmendorf tear strength in the width direction of the substrate is 0.5 N or less and the Elmendorf tear strength in the length direction of the substrate is 1 N or more in the present surface protection film.
[0017] In addition, as described above, the Elmendorf tear strength of the present surface protection film in the substrate width direction is less than 0.5N, and the Elmendorf tear strength in the substrate length direction is more than 1N. Such a structure is suitable for achieving good hand tearing properties in the present surface protection film along the substrate width direction where the Elmendorf tear strength is relatively intentionally low to less than 0.5N. At the same time, the structure of more than 1N in which the Elmendorf tear strength in the substrate length direction is more than twice that in the substrate width direction is suitable for improving the directionality of tearing along the substrate width direction in the present surface protection film. Therefore, the structure is suitable for causing the peeling force to act on the substrate length direction of the film when the present surface protection film is in a state of being attached to the adherend, so that the film is properly peeled off from the adherend without cracking. Specifically, it is suitable for causing the peeling force to act on the substrate length direction of the film when the present surface protection film is attached to the adherend and then attached again (reprocessing operation) so that the film is properly peeled off from the adherend without cracking. A surface protective film that is easily torn not only in the substrate width direction but also in the substrate length direction tends to be easily cracked during peeling in reprocessing operations and is difficult to be properly peeled off from the adherend. A surface protective film that has cracked cannot be used for re-lamination. In contrast, the present surface protective film has an Elmendorf tear strength in the substrate length direction that is sufficiently greater than the Elmendorf tear strength in the substrate width direction that is suitable for achieving good hand tearability in the substrate width direction, and is therefore suitable for being properly peeled off from the adherend without cracking during reprocessing operations.
[0018] As described above, the present surface protection film is suitable for achieving both good hand-tearability and high reworkability while having a polyester-based substrate.
[0019] The thickness of the pressure-sensitive adhesive layer is preferably 5 μm or more. Such a configuration is suitable for achieving sufficient adhesiveness of the surface protection film to an adherend.
[0020] The haze of the present surface protection film in the thickness direction is preferably 3% or less. Such a structure is suitable for a surface protection film for use in optical components, for example. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a partial cross-sectional view of a surface protection film according to one embodiment of the present invention.
[0022] Reference numerals
[0023] X Surface Protection Film
[0024] 11. Substrate
[0025] 12 Adhesive layer DETAILED DESCRIPTION
[0026] Figure 1: is a partial cross-sectional view of a surface protection film X according to one embodiment of the present invention. The surface protection film X has a laminated structure including a substrate 11 as a transparent substrate and an adhesive layer 12. For example, the surface protection film X can be applied to the surface of various optical components assembled in a flat panel display for the purpose of protecting the surface of the optical components during the manufacturing process, inspection process, transportation process, etc.
[0027] The substrate 11 included in the surface protection film X is a portion that functions as a support in the surface protection film X and is a light-transmitting polyester-based substrate that is uniaxially stretched in the substrate width direction.
[0028] The polyester-based substrate refers to a substrate such as a film or sheet containing a polyester-based resin in the largest weight ratio among the constituent materials. Examples of the constituent materials of the substrate 11 include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and poly(1,4-cyclohexanedimethanol terephthalate).
[0029] The polyester substrate uniaxially stretched in the substrate width direction refers to a polyester substrate that has been subjected to uniaxial stretching treatment in the width direction (TD) orthogonal to the flow direction or longitudinal direction (MD) of the film-shaped extruded body after extrusion molding of the raw resin material in the polyester substrate manufacturing process. The stretching ratio in the width direction of the substrate 11 as such a polyester substrate uniaxially stretched in the width direction is preferably 2.5 times or more, more preferably 3 times or more. In addition, the stretching ratio is preferably 6 times or less, more preferably 5.5 times or less.
[0030] The thickness of the substrate 11 is 75 μm or more, preferably 80 μm or more. The thickness of the substrate 11 is preferably 150 μm or less, more preferably 125 μm or less.
[0031] The in-plane phase difference of the substrate 11 is preferably 1500 nm or more, more preferably 3000 nm or more, and more preferably 6000 nm or more. In the present embodiment, the in-plane phase difference of the substrate 11 refers to the phase difference generated between the polarized light component (abnormal light) vibrating in the slow axis direction and the polarized light component (normal light) vibrating in the fast axis direction in two optical principal axes (slow axis and fast axis) orthogonal in the plane parallel to the main surface of the substrate 11, which is related to the birefringence when light with a wavelength of 590 nm is transmitted through the substrate 11 at 23°C. When the refractive index of the abnormal light (relatively large) is set to nx, the refractive index of the normal light (relatively small) is set to ny, and the thickness of the substrate 11 is set to d (nm), the in-plane phase difference is a value represented by (nx-ny)×d.
[0032] The surface of the substrate 11 on the adhesive layer 12 side may be subjected to a surface treatment for improving adhesion to the adhesive layer. Examples of such surface treatments include physical treatments such as corona treatment and plasma treatment, and chemical treatments such as primer treatment.
[0033] The adhesive layer 12 of the surface protection film X contains an adhesive as a main agent and has light transmittance. The main agent refers to the component that occupies the largest weight proportion among the components contained. The adhesive layer 12 contains, for example, at least one selected from the group consisting of an acrylic polymer as an acrylic adhesive, a polyurethane as a polyurethane adhesive, a polysiloxane adhesive, and a rubber adhesive. From the viewpoint of simultaneously achieving the required degree of adhesive force and high transparency of the adhesive layer of the surface protection film, it is preferred to use an acrylic polymer as the adhesive in the adhesive layer 12. In addition, the adhesive layer 12 has an adhesive surface 12a that can be attached to an adherend.
[0034] When the adhesive layer 12 contains an acrylic polymer as an acrylic adhesive, the acrylic polymer preferably contains monomer units derived from an alkyl acrylate having a linear or branched alkyl group and / or an alkyl methacrylate having a linear or branched alkyl group as the main monomer units with the largest weight ratio. Hereinafter, "(meth)acrylic acid" means "acrylic acid" and / or "methacrylic acid".
[0035] Examples of the (meth)acrylic acid alkyl ester having a linear or branched alkyl group as a monomer unit for forming the acrylic polymer, that is, the (meth)acrylic acid alkyl ester having a linear or branched alkyl group contained in the monomer component for forming the acrylic polymer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, and (meth)acrylate. Alkyl (meth)acrylates having a linear or branched alkyl group having 1 to 20 carbon atoms, such as 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. As the alkyl (meth)acrylate used for the acrylic polymer, one alkyl (meth)acrylate may be used, or two or more alkyl (meth)acrylates may be used. In the present embodiment, as the alkyl (meth)acrylate used for the acrylic polymer, at least one selected from the group consisting of n-butyl acrylate, 2-ethylhexyl acrylate, and isostearyl acrylate is preferably used.
[0036] The ratio of monomer units of (meth) alkyl acrylates derived from linear or branched alkyl groups in the acrylic polymer is preferably 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, and more preferably 90% by weight or more. That is, the ratio of (meth) alkyl acrylates in the monomer component composition of the raw material for forming the acrylic polymer is preferably 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, and more preferably 90% by weight or more. The acrylic polymer has a monomer unit composition derived from a monomer component composition having such a ratio of (meth) alkyl acrylates. The composition of the ratio of (meth) alkyl acrylates with linear or branched alkyl groups is suitable in terms of the basic characteristics such as the adhesiveness of the acrylic polymer as an acrylic adhesive appropriately exhibited in the adhesive layer formed by containing the acrylic polymer.
[0037] The acrylic polymer contained in the adhesive layer 12 may contain a monomer unit derived from an alicyclic monomer. As the alicyclic monomer used to form the monomer unit of the acrylic polymer, that is, as the alicyclic monomer contained in the monomer component used to form the acrylic polymer, for example, cycloalkyl (meth)acrylates, (meth)acrylates having a bicyclic hydrocarbon ring, and (meth)acrylates having a hydrocarbon ring of three or more rings can be cited. As cycloalkyl (meth)acrylates, for example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate can be cited. As (meth)acrylates having a bicyclic hydrocarbon ring, for example, bornyl (meth)acrylate and isobornyl (meth)acrylate can be cited. As (meth)acrylates having three or more hydrocarbon rings, for example, tetrahydrodicyclopentadienyl (meth)acrylate, tetrahydrodicyclopentadienyloxyethyl (meth)acrylate, tetrahydrotricyclopentadienyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate can be cited. As alicyclic monomers for acrylic polymers, one alicyclic monomer can be used, or two or more alicyclic monomers can be used. In the present embodiment, as alicyclic monomers for acrylic polymers, at least one selected from the group consisting of cyclohexyl acrylate, cyclohexyl methacrylate, isobornyl acrylate, and isobornyl methacrylate is preferably used.
[0038] From the viewpoint of achieving appropriate flexibility in a pressure-sensitive adhesive layer containing the acrylic polymer, the ratio of the monomer unit derived from the alicyclic monomer in the acrylic polymer is preferably 5 to 60 wt %, more preferably 10 to 50 wt %.
[0039] The acrylic polymer contained in the adhesive layer 12 may contain a monomer unit derived from a hydroxyl-containing monomer. A hydroxyl-containing monomer is a monomer having at least one hydroxyl group in the monomer unit. When the acrylic polymer in the adhesive layer 12 contains a hydroxyl-containing monomer unit, the adhesive layer 12 is easy to obtain adhesiveness and appropriate cohesive force.
[0040] As the hydroxyl-containing monomer used to form the monomer unit of the acrylic polymer, that is, as the hydroxyl-containing monomer contained in the monomer component used to form the acrylic polymer, for example, hydroxyl-containing (meth)acrylate, vinyl alcohol and allyl alcohol can be mentioned. As the hydroxyl-containing (meth)acrylate, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate can be mentioned. As the hydroxyl-containing monomer used for the acrylic polymer, one hydroxyl-containing monomer can be used, or two or more hydroxyl-containing monomers can be used. In this embodiment, as the hydroxyl-containing monomer for the acrylic polymer, at least one selected from the group consisting of 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate and 4-hydroxybutyl methacrylate is preferably used.
[0041] The proportion of monomer units derived from hydroxyl-containing monomers in the acrylic polymer is preferably 1% by weight or more, more preferably 2% by weight or more, more preferably 3% by weight or more, more preferably 5% by weight or more, more preferably 7% by weight or more, more preferably 10% by weight or more. The proportion of monomer units derived from hydroxyl-containing monomers in the acrylic polymer is preferably 20% by weight or less, more preferably 18% by weight or less. These configurations regarding the proportion of hydroxyl-containing monomers are suitable for achieving adhesiveness and appropriate cohesive force in the adhesive layer formed by containing the acrylic polymer.
[0042] The acrylic polymer contained in the adhesive layer 12 may contain a monomer unit derived from a nitrogen-containing monomer. The nitrogen-containing monomer is a monomer having at least one nitrogen atom in the monomer unit. When the acrylic polymer in the adhesive layer 12 contains a nitrogen-containing monomer unit, the adhesive layer 12 is easy to obtain hardness and good adhesive reliability.
[0043] Examples of nitrogen-containing monomers used to form the monomer units of the acrylic polymers, i.e., nitrogen-containing monomers contained in the monomer components used to form the acrylic polymers, include N-vinyl cyclic amides and (meth)acrylamides. Examples of N-vinyl cyclic amides used as nitrogen-containing monomers include N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3- Oxazine-2-one and N-vinyl-3,5-morpholinedione. (Meth)acrylamides as nitrogen atom-containing monomers include, for example: (meth)acrylamide, N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-n-butyl (meth)acrylamide, N-octyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide and N,N-diisopropyl (meth)acrylamide. As nitrogen atom-containing monomers for acrylic polymers, one nitrogen atom-containing monomer can be used, or two or more nitrogen atom-containing monomers can be used. In the present embodiment, as a nitrogen atom-containing monomer for acrylic polymers, N-vinyl-2-pyrrolidone is preferably used.
[0044] For the adhesive layer formed by containing the acrylic polymer, from the viewpoint of achieving appropriate hardness, adhesiveness and transparency, the ratio of the monomer units derived from the nitrogen-containing monomer in the acrylic polymer is preferably 1% by weight or more, more preferably 3% by weight or more, and more preferably 5% by weight or more. In addition, for the adhesive layer formed by containing the acrylic polymer, from the viewpoint of achieving sufficient transparency and suppressing excessive hardening to achieve good adhesive reliability, the ratio of the monomer units derived from the nitrogen-containing monomer in the acrylic polymer is preferably 30% by weight or less, and more preferably 25% by weight or less.
[0045] The acrylic polymer contained in the adhesive layer 12 may contain a monomer unit derived from a carboxyl group-containing monomer. A carboxyl group-containing monomer is a monomer having at least one carboxyl group in the monomer unit. When the acrylic polymer in the adhesive layer 12 contains a carboxyl group-containing monomer unit, the adhesive layer 12 may sometimes obtain good adhesive reliability.
[0046] As the carboxyl-containing monomer used to form the monomer unit of the acrylic polymer, i.e., as the carboxyl-containing monomer contained in the monomer component used to form the acrylic polymer, for example, (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid and isocrotonic acid can be cited. As the carboxyl-containing monomer used for the acrylic polymer, one carboxyl-containing monomer can be used, or two or more carboxyl-containing monomers can be used. In the present embodiment, acrylic acid is preferably used as the carboxyl-containing monomer used for the acrylic polymer.
[0047] From the viewpoint of obtaining the contribution of interaction with the polar group when there is a polar group on the surface of the adherend in the adhesive layer formed by containing the acrylic polymer, thereby ensuring good adhesive reliability, the proportion of the monomer unit derived from the carboxyl group-containing monomer in the acrylic polymer is preferably 0.1% by weight or more, more preferably 0.5% by weight or more. In addition, from the viewpoint of suppressing excessive hardening of the adhesive layer formed by containing the acrylic polymer, thereby achieving good adhesive reliability, the proportion of the monomer unit derived from the carboxyl group-containing monomer in the acrylic polymer is preferably 20% by weight or less, more preferably 15% by weight or less.
[0048] The acrylic polymer contained in the adhesive layer 12 may have a cross-linked structure derived from a multifunctional (meth)acrylate as a copolymerizable cross-linking agent. As multifunctional (meth)acrylates, for example, 1,6-hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, and vinyl (meth)acrylate. As multifunctional (meth)acrylates used for acrylic polymers, one type of multifunctional (meth)acrylate may be used, or two or more types of multifunctional (meth)acrylates may be used. In the present embodiment, as the polyfunctional (meth)acrylate used for the acrylic polymer, at least one selected from the group consisting of 1,6-hexanediol diacrylate, dipentaerythritol hexaacrylate, and trimethylolpropane triacrylate is preferably used.
[0049] The proportion of monomer units derived from multifunctional (meth)acrylate in the acrylic polymer is preferably 0.01% by weight or more, more preferably 0.03% by weight or more, and more preferably 0.05% by weight or more. The proportion of monomer units derived from multifunctional (meth)acrylate in the acrylic polymer is preferably 1% by weight or less, and more preferably 0.5% by weight or less. These configurations regarding the proportion of multifunctional (meth)acrylate are suitable for achieving appropriate hardness and adhesiveness in the adhesive layer formed by containing the acrylic polymer.
[0050] When the pressure-sensitive adhesive layer 12 contains the acrylic polymer as described above as a pressure-sensitive adhesive, the content of the acrylic polymer in the pressure-sensitive adhesive layer 12 is, for example, 85% by weight to 100% by weight.
[0051] From the viewpoint of achieving high adhesiveness at room temperature, the adhesive layer 12 may contain, for example, an acrylic oligomer having a raw material monomer composition different from that of the acrylic polymer. When the adhesive layer 12 contains such an acrylic oligomer, the content of the acrylic oligomer in the adhesive layer 12 is, for example, 0.1 to 20 parts by weight relative to 100 parts by weight of the adhesive or acrylic polymer in the adhesive layer 12.
[0052] The oligomer is preferably a polymer containing a monomer unit derived from a (meth)acrylate having a cyclic structure (ring-containing (meth)acrylate) and a monomer unit derived from an alkyl (meth)acrylate having a linear or branched alkyl group.
[0053] As the ring-containing (meth)acrylate used to form the monomer unit of the above-mentioned oligomer, that is, as the ring-containing (meth)acrylate contained in the monomer component used to form the oligomer, for example, cycloalkyl (meth)acrylate, (meth)acrylate having a bicyclic hydrocarbon ring, (meth)acrylate having a hydrocarbon ring of three or more rings, and (meth)acrylate having an aromatic ring can be cited. As the cycloalkyl (meth)acrylate, for example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate can be cited. As the (meth)acrylate having a bicyclic hydrocarbon ring, for example, bornyl (meth)acrylate and isobornyl (meth)acrylate can be cited. As (meth)acrylates having a hydrocarbon ring of three or more rings, for example, tetrahydrodicyclopentadienyl (meth)acrylate, tetrahydrodicyclopentadienyloxyethyl (meth)acrylate, tetrahydrotricyclopentadienyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate can be cited. As (meth)acrylates having an aromatic ring, for example, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate can be cited. As a ring-containing (meth)acrylate for an oligomer, one ring-containing (meth)acrylate can be used, or two or more ring-containing (meth)acrylates can be used. In the present embodiment, as a ring-containing (meth)acrylate for an oligomer, it is preferred to use at least one selected from the group consisting of tetrahydrodicyclopentadienyl acrylate and tetrahydrodicyclopentadienyl methacrylate.
[0054] From the viewpoint of achieving appropriate flexibility in the pressure-sensitive adhesive layer 12 formed by containing the oligomer, the ratio of the monomer unit derived from the ring-containing (meth)acrylate in the oligomer is preferably 10 to 90 wt %, more preferably 20 to 80 wt %, and even more preferably 35 to 80 wt %.
[0055] Examples of the alkyl (meth)acrylate having a linear or branched alkyl group as the monomer unit for forming the oligomer, that is, the alkyl (meth)acrylate having a linear or branched alkyl group contained in the monomer component for forming the oligomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, Alkyl (meth)acrylates having a linear or branched alkyl group having 1 to 20 carbon atoms, such as 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. As the alkyl (meth)acrylate used for the above-mentioned oligomer, one alkyl (meth)acrylate may be used, or two or more alkyl (meth)acrylates may be used. In the present embodiment, methyl methacrylate is preferably used as the alkyl (meth)acrylate used for the above-mentioned oligomer.
[0056] From the viewpoint of achieving an appropriate elastic modulus in a pressure-sensitive adhesive layer formed by containing the oligomer, the proportion of the monomer unit derived from an alkyl (meth)acrylate having a linear or branched alkyl group in the oligomer is preferably 10 to 90% by weight, more preferably 15 to 80% by weight, and even more preferably 20 to 60% by weight.
[0057] The oligomer may contain monomer units derived from carboxyl group-containing monomers, amide group-containing monomers, amino group-containing monomers, cyano group-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, isocyanate group-containing monomers, and imide group-containing monomers.
[0058] The weight average molecular weight (Mw) of the oligomer is, for example, 1000 to 30000, preferably 1000 to 20000, and more preferably 1500 to 10000. From the viewpoint of ensuring good adhesive force in the adhesive layer formed by containing the oligomer, the weight average molecular weight of the oligomer is preferably 1000 or more. On the other hand, from the viewpoint of ensuring adhesive force, especially at room temperature, in the adhesive layer formed by containing the oligomer, the weight average molecular weight of the oligomer is preferably 30000 or less.
[0059] The weight average molecular weight of the oligomer can be measured by gel permeation chromatography (GPC). For example, the weight average molecular weight (Mw) can be determined as a standard polystyrene conversion value using a GPC measuring apparatus (trade name "HLC-8120GPC", manufactured by Tosoh Corporation) under the following measuring conditions.
[0060] ・Column: TSKgel SuperAWM-H (upstream side, manufactured by Tosoh Corporation), TSKgel SuperAW4000 (manufactured by Tosoh Corporation), and TSKgel SuperAW2500 (downstream side, manufactured by Tosoh Corporation) connected in series ・Column size: 6.0 mm φ × 150 mm for each column ・Column temperature (measurement temperature): 40°C ・Eluent: Tetrahydrofuran (THF) ・Flow rate: 0.4 mL / min ・Sample injection volume: 20 μL ・Sample concentration: Approximately 2.0 g / L (tetrahydrofuran solution) ・Standard sample: Polystyrene ・Detector: Differential refractometer (RI)
[0061] The adhesive layer 12 may contain a silane coupling agent. Examples of the silane coupling agent include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and N-phenylaminopropyltrimethoxysilane. Examples of the silane coupling agent include commercial products such as "KBM-403" (manufactured by Shin-Etsu Chemical Co., Ltd.). γ-glycidoxypropyltrimethoxysilane is preferred as the silane coupling agent.
[0062] When the adhesive layer 12 contains a silane coupling agent, the content of the silane coupling agent in the adhesive layer 12 is preferably 0.01 parts by weight or more, and more preferably 0.02 parts by weight or more, relative to 100 parts by weight of the adhesive or acrylic polymer in the adhesive layer 12. In addition, the content of the silane coupling agent in the adhesive layer 12 is preferably 1 part by weight or less, and more preferably 0.5 parts by weight or less, relative to 100 parts by weight of the acrylic polymer. This configuration regarding the content of the silane coupling agent is suitable for achieving high adhesion under humidified conditions, particularly high adhesion to glass, in the adhesive layer 12 formed by containing the silane coupling agent.
[0063] The adhesive layer 12 may contain an ultraviolet absorber. An ultraviolet absorber is a chemical substance that can efficiently absorb ultraviolet rays and convert the absorbed energy into heat, infrared rays, etc. and release it. Examples of such ultraviolet absorbers include benzotriazole ultraviolet absorbers, hydroxyphenyltriazine ultraviolet absorbers, salicylate ultraviolet absorbers, benzophenone ultraviolet absorbers, hydroxybenzophenone ultraviolet absorbers, and cyanoacrylate ultraviolet absorbers. The adhesive layer 12 may contain one ultraviolet absorber or two or more ultraviolet absorbers.
[0064] Examples of the benzotriazole ultraviolet absorber include 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole (trade name "TINUVIN PS", manufactured by BASF), 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxyphenylpropionic acid, and carbon 7-9 alkyl esters (trade name "TINUVIN 384-2", manufactured by BASF), a mixture of octyl 3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazol-2-yl)phenyl]propionate and 2-ethylhexyl 3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazol-2-yl)phenyl]propionate (trade name "TINUVIN 109", manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (trade name "TINUVIN 900", manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (trade name "TINUVIN 928", manufactured by BASF), reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl) propionate and polyethylene glycol 300 (trade name "TINUVIN 1130", manufactured by BASF), 2-(2H-benzotriazol-2-yl)-p-cresol (trade name "TINUVIN P", manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (trade name "TINUVIN 234", manufactured by BASF), 2-[5-chloro-2H-benzotriazol-2-yl]-4-methyl-6-tert-butylphenol (trade name "TINUVIN 326", manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-di-tert-amylphenol (trade name "TINUVIN 328", manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (trade name "TINUVIN 329", manufactured by BASF), 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol] (trade name "TINUVIN 360", manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol (trade name "TINUVIN 571", manufactured by BASF), 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole (trade name "Sumisorb 250", manufactured by Sumitomo Chemical Co., Ltd.) and 2,2'-Methylenebis[6-(2H-benzotriazol-2-yl)-4-tert-octylphenol] (trade name "ADK STAB LA-31", manufactured by ADK Co., Ltd.),
[0065] Examples of hydroxyphenyltriazine ultraviolet absorbers include the reaction product of 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-hydroxyphenol and [(alkyloxy group having 10 to 16 carbon atoms)methyl]oxirane (trade name "TINUVIN 400", manufactured by BASF), 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl]-5-[3-(dodecyloxy)-2-hydroxypropoxy]phenol), reaction product of 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-ethylhexyl glycidate (trade name "TINUVIN 405", manufactured by BASF), 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (trade name "TINUVIN 460", manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxyphenol (trade name "TINUVIN 1577", manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol (trade name "ADK STAB LA-46", manufactured by ADK Co., Ltd.), and 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (trade name "TINUVIN 479", manufactured by BASF).
[0066] Examples of the salicylate-based ultraviolet absorber include phenyl 2-acryloxybenzoate, phenyl 2-acryloxy-3-methylbenzoate, phenyl 2-acryloxy-4-methylbenzoate, phenyl 2-acryloxy-5-methylbenzoate, phenyl 2-acryloxy-3-methoxybenzoate, phenyl 2-hydroxybenzoate, phenyl 2-hydroxy-3-methylbenzoate, phenyl 2-hydroxy-4-methylbenzoate, phenyl 2-hydroxy-5-methylbenzoate, phenyl 2-hydroxy-3-methoxybenzoate, and phenyl 3,5-di-tert-butyl-4-hydroxybenzoate (trade name: "TINUVIN 120", manufactured by BASF).
[0067] Examples of the benzophenone-based ultraviolet absorber and the hydroxybenzophenone-based ultraviolet absorber include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-octyloxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 4-benzyloxy-2-hydroxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone (trade name "KEMISORB 111", manufactured by Chemipro Chemicals Co., Ltd.), 2,2',4,4'-tetrahydroxybenzophenone (trade name "SEESORB 106", manufactured by Shipro Chemicals Co., Ltd.), and 2,2'-dihydroxy-4,4'-dimethoxybenzophenone.
[0068] Examples of the cyanoacrylate-based ultraviolet absorber include 2-cyanoacrylate alkyl esters, 2-cyanoacrylate cycloalkyl esters, 2-cyanoacrylate alkoxyalkyl esters, 2-cyanoacrylate alkenyl esters, and 2-cyanoacrylate alkynyl esters.
[0069] From the viewpoint of having high ultraviolet absorbency and high light stability, or from the viewpoint of easily obtaining a highly transparent adhesive layer 12, the ultraviolet absorber contained in the adhesive layer 12 is preferably at least one selected from the group consisting of benzotriazole ultraviolet absorbers, hydroxyphenyltriazine ultraviolet absorbers, and benzophenone ultraviolet absorbers. The ultraviolet absorber contained in the adhesive layer 12 is more preferably a benzotriazole ultraviolet absorber in which a phenyl group having a hydrocarbon group having 6 or more carbon atoms and a hydroxyl group as a substituent is bonded to a nitrogen atom constituting a benzotriazole ring.
[0070] When the adhesive layer 12 contains an ultraviolet absorber, from the viewpoint of achieving high ultraviolet absorbency by controlling the transmittance of light having a wavelength of 350 nm in the adhesive layer 12, the content of the ultraviolet absorber in the adhesive layer 12 is preferably 0.01 parts by weight or more, more preferably 0.05 parts by weight or more, and more preferably 0.1 parts by weight or more, based on 100 parts by weight of the adhesive or acrylic polymer in the adhesive layer 12. Furthermore, from the viewpoint of suppressing the occurrence of yellowing of the adhesive accompanying the addition of the ultraviolet absorber in the adhesive layer 12 and achieving excellent optical properties and high transparency, the content of the ultraviolet absorber in the adhesive layer 12 is preferably 10 parts by weight or less, more preferably 9 parts by weight or less, and more preferably 8 parts by weight or less, based on 100 parts by weight of the adhesive or acrylic polymer in the adhesive layer 12.
[0071] The adhesive layer 12 may contain a light stabilizer. When the adhesive layer 12 contains a light stabilizer, it is preferred that it also contains an ultraviolet absorber. A light stabilizer is a chemical substance that can capture free radicals that can be generated by irradiating light such as ultraviolet rays. As the light stabilizer, for example, amine light stabilizers such as phenolic light stabilizers, phosphorus-containing light stabilizers, thioether light stabilizers, and hindered amine stabilizers can be cited. The adhesive layer 12 may contain one light stabilizer or two or more light stabilizers.
[0072] Examples of the phenolic light stabilizer include 2,6-di-tert-butyl-4-methylphenol, 4-hydroxymethyl-2,6-di-tert-butylphenol, 2,6-di-tert-butyl-4-ethylphenol, butylated hydroxyanisole, n-octadecyl 3-(4-hydroxy-3,5-di-tert-butylphenyl)propionate, distearyl (4-hydroxy-3-methyl-5-tert-butyl)benzylmalonate, tocopherol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 4,4'-methylenebis(4-hydroxy-3,5-di-tert-butylphenyl)propionate, and 4,4'-methylenebis(4-hydroxy-3-methyl-5-tert-butyl)benzylmalonate. -Butylenebis(6-tert-butyl-m-cresol), 4,4'-thiobis(6-tert-butyl-m-cresol), styrenated phenol, N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid), calcium bis(ethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, 1,6-hexanediol-bis[3-(3,5 -di-tert-butyl-4-hydroxyphenyl) propionate], 2,2'-methylenebis(4-methyl-6-cyclohexylphenol), 2,2'-methylenebis[6-(1-methylcyclohexyl)p-cresol], 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid, triethylene glycol bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate], 2,2'-oxalamidobis[ethyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], 6-(4-hydroxy-3, terephthalic acid bis[2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl]ester, 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane, and 3,9-bis{2-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane.
[0073] Examples of the phosphorus-containing light stabilizer include tris(nonylphenyl) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tris[2-tert-butyl-4-(3-tert-butyl-4-hydroxy-5-methylphenylthio)-5-methylphenyl] phosphite, tridecyl phosphite, dioctyl phosphite, monodecyl phosphite, ditridecyl pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, di(nonylphenyl) pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphite, and di(tridecyl) pentaerythritol diphosphite. Tetraol diphosphite bis(2,4,6-tri-tert-butylphenyl) ester, isopropylidene bisphenol diphosphite tetra(tridecyl) ester, 4,4'-n-butylidene bis(2-tert-butyl-5-methylphenol) diphosphite tetra(tridecyl) ester, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane triphosphite hexa(tridecyl) ester, biphenylene diphosphite tetra(2,4-di-tert-butylphenyl) ester, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and tris(2-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphin-6-yl)oxy]ethyl)amine.
[0074] Examples of the thioether light stabilizer include dialkyl thiodipropionate compounds such as dilauryl thiodipropionate, dimyristyl thiodipropionate, and distearyl thiodipropionate; and β-alkylmercaptopropionate compounds of polyhydric alcohols such as tetrakis[methylene(3-dodecylthio)propionate]methane.
[0075] Examples of amine light stabilizers include a polymer of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol (trade name "TINUVIN 622", manufactured by BASF), and a 1:1 reaction product of the polymer and N,N',N'',N'''-tetrakis(4,6-bis(butyl-(N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)triazine-2-yl)-4,7-diazadecane-1,10-diamine (trade name "TINUVIN 119", manufactured by BASF), poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{2,2,6,6-tetramethyl-4-piperidinyl}imino]hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino} (trade name "TINUVIN 944", manufactured by BASF), bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (trade name "TINUVIN 770", manufactured by BASF), reaction products of bis(2,2,6,6-tetramethyl-1-(octyloxy)-4-piperidinyl) sebacate with 1,1-dimethylethyl hydroperoxide and octane (trade name "TINUVIN 123", manufactured by BASF), bis(1,2,2,6,6-pentamethyl-4-piperidinyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate (trade name "TINUVIN 144", manufactured by BASF), reaction product of cyclohexane and peroxide N-butyl-2,2,6,6-tetramethyl-4-piperidinamine-2,4,6-trichloro-1,3,5-triazine with 2-aminoethanol (trade name "TINUVIN 152", manufactured by BASF), mixture of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate (trade name "TINUVIN 292", manufactured by BASF) and a mixed ester of 1,2,3,4-butanetetracarboxylic acid, 1,2,2,6,6-pentamethyl-4-piperidinol and 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane (trade name "ADK STAB LA-63P", manufactured by ADK Corporation). As the amine stabilizer, a hindered amine stabilizer is particularly preferred.
[0076] When the adhesive layer 12 contains a light stabilizer, the content of the light stabilizer in the adhesive layer 12 is preferably 0.1 parts by weight or more, and more preferably 0.2 parts by weight or more, based on 100 parts by weight of the adhesive or acrylic polymer in the adhesive layer 12, from the viewpoint of achieving sufficient light resistance in the adhesive layer 12. In addition, from the viewpoint of suppressing coloration due to the light stabilizer in the adhesive layer 12 and achieving high transparency, the content of the light stabilizer in the adhesive layer 12 is preferably 5 parts by weight or less, and more preferably 3 parts by weight or less, based on 100 parts by weight of the adhesive or acrylic polymer in the adhesive layer 12.
[0077] The adhesive or acrylic polymer contained in the adhesive layer 12 can be cross-linked by a cross-linking agent other than the copolymerizable cross-linking agent. By cross-linking the adhesive or acrylic polymer by the cross-linking agent, the gel fraction of the adhesive layer 12 can be adjusted. Examples of such cross-linking agents include isocyanate cross-linking agents, epoxy cross-linking agents, melamine cross-linking agents, peroxide cross-linking agents, urea cross-linking agents, metal alkoxide cross-linking agents, metal chelate cross-linking agents, metal salt cross-linking agents, carbodiimide cross-linking agents, Oxazoline crosslinking agents, aziridine crosslinking agents and amine crosslinking agents. The adhesive layer 12 may contain one type of such crosslinking agent, or may contain two or more types of such crosslinking agents. In this embodiment, it is preferred to use an isocyanate crosslinking agent and / or an epoxy crosslinking agent.
[0078] As isocyanate crosslinking agents, for example, lower aliphatic polyisocyanates, alicyclic polyisocyanates and aromatic polyisocyanates can be cited. As lower aliphatic polyisocyanates, for example, 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate and 1,6-hexamethylene diisocyanate can be cited. As alicyclic polyisocyanates, for example, cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated toluene diisocyanate and hydrogenated xylene diisocyanate can be cited. As aromatic polyisocyanates, for example, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate and xylylene diisocyanate can be cited. In addition, examples of isocyanate crosslinking agents include commercially available products such as trimethylolpropane / toluene diisocyanate adduct (trade name "Coronate L", manufactured by Nippon Polyurethane Industries, Ltd.), trimethylolpropane / hexamethylene diisocyanate adduct (trade name "Coronate HL", manufactured by Nippon Polyurethane Industries, Ltd.), and trimethylolpropane / xylylene diisocyanate adduct (trade name "Takenate D-110N", manufactured by Mitsui Chemicals, Inc.).
[0079] Examples of epoxy crosslinking agents (polyfunctional epoxides) include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, tris(2-hydroxyethyl)isocyanurate triglycidyl ether, resorcinol diglycidyl ether, and bisphenol S diglycidyl ether. In addition, epoxy crosslinking agents include epoxy resins having two or more epoxy groups, and commercial products such as "TETRAD C" (manufactured by Mitsubishi Gas Chemical Co., Ltd.) are also included as epoxy crosslinking agents.
[0080] When the adhesive layer 12 contains the crosslinking agent as described above for crosslinking acrylic polymers, the content of the crosslinking agent in the adhesive layer 12 is preferably 0.001 parts by weight or more, more preferably 0.01 parts by weight or more, based on 100 parts by weight of the adhesive or acrylic polymer in the adhesive layer 12, from the viewpoint of achieving sufficient adhesive reliability to the adherend in the adhesive layer 12. In addition, from the viewpoint of achieving good adhesive strength by showing appropriate flexibility in the adhesive layer 12, the content of the crosslinking agent in the adhesive layer 12 is preferably 10 parts by weight or less, more preferably 5 parts by weight or less, based on 100 parts by weight of the adhesive or acrylic polymer in the adhesive layer 12.
[0081] The adhesive layer 12 may further contain additives such as a crosslinking accelerator, a tackifying resin, an anti-aging agent, a filler, a colorant such as a pigment or dye, an antioxidant, a chain transfer agent, a plasticizer, a softener, a surfactant, and an antistatic agent as needed. Examples of the tackifying resin include rosin derivatives, polyterpene resins, petroleum resins, and oil-soluble phenol resins.
[0082] From the viewpoint of achieving sufficient adhesive force of the surface protection film X to the adherend on the adhesive layer 12 side, the thickness of the adhesive layer 12 is preferably 5 μm or more, more preferably 10 μm or more, and more preferably 15 μm or more. From the viewpoint of ease of formation, the thickness of the adhesive layer 12 is preferably 1000 μm or less, more preferably 900 μm or less, and more preferably 800 μm or less.
[0083] In the surface protection film X having a laminated structure including the substrate 11 and the adhesive layer 12 as described above, the Elmendorf tear strength in the width direction of the substrate is 0.5N or less, and the Elmendorf tear strength in the length direction of the substrate is 1N or more. The Elmendorf tear strength in the width direction of the substrate of the surface protection film X is preferably 0.45N or less, more preferably 0.4N or less, and more preferably 0.3N or less. The Elmendorf tear strength in the length direction of the substrate of the surface protection film X is preferably 1.1N or more, more preferably 1.3N or more, and more preferably 1.5N or more. The Elmendorf tear strength is a value measured in accordance with JIS K7128-2.
[0084] In addition, the haze in the thickness direction of the optical surface protection film X is preferably 3% or less, more preferably 2.5% or less, more preferably 2% or less, more preferably 1.5% or less, and more preferably 1% or less. The haze is a value measured in accordance with JIS K 7136. The total light transmittance in the visible light wavelength range of the surface protection film X is, for example, 85% or more. The total light transmittance is a value measured in accordance with JIS K7361-1.
[0085] The surface protection film X may be provided with a release liner (spacer) in the form of covering the adhesive surface 12a of the adhesive layer 12. The release liner is an element for protecting the adhesive layer 12 of the surface protection film X from being exposed, and is peeled off from the surface protection film X when the surface protection film X is attached to the adherend. As the release liner, for example: a substrate with a release treatment layer, a low-adhesive substrate containing a fluorine-containing polymer, and a low-adhesive substrate containing a non-polar polymer can be cited. The surface of the release liner can be subjected to a demolding treatment, an antifouling treatment, or an antistatic treatment. The thickness of the release liner is, for example, 5 μm to 200 μm. Specifically, the surface protection film X can be in the form of a sheet with a release liner covering the adhesive surface 12a of the adhesive layer 12, or it can be in the form of being wound into a roll-shaped form in which the substrate 11 of the surface protection film X and the adhesive layer 12 are alternately arranged without a release liner.
[0086] The surface protection film X configured as described above can be manufactured, for example, by forming the adhesive layer 12 and then bonding the adhesive layer 12 to the substrate 11. The adhesive layer 12 can be formed, for example, by coating an adhesive composition for forming the adhesive layer 12 on a predetermined release liner to form an adhesive composition layer, further laminating a release liner on the adhesive composition layer, and curing the adhesive composition between the release liners.
[0087] As the adhesive composition for forming the adhesive layer 12, for example, an adhesive composition that can be cured by irradiating active energy rays so that the polymerization reaction proceeds. That is, the adhesive layer 12 is, for example, a cured product of an active energy ray-curable adhesive composition. The active energy ray-curable adhesive composition for forming an acrylic adhesive layer contains at least monomers, oligomers and photopolymerization initiators for forming acrylic polymers. The monomers and oligomers in the composition can be provided in the form of a so-called partial polymer of a monomer mixture of a prescribed composition for forming an acrylic polymer. In addition, the adhesive composition may contain other components used as required as components of the adhesive layer 12 to be formed. As for the active energy rays irradiated to the active energy ray-curable adhesive composition for curing the adhesive layer 12, for example, ultraviolet rays, α rays, β rays, γ rays, neutron rays and electron rays can be listed, preferably ultraviolet rays. For the active energy ray-curable adhesive composition for forming an acrylic adhesive layer irradiated with active energy rays, an initiation reaction is generated by activation of the photopolymerization initiator, and the polymerization reaction proceeds toward the formation of an acrylic polymer. When active energy ray irradiation such as ultraviolet ray irradiation is used as a curing method for the curable adhesive composition for forming the adhesive layer, it is easy to obtain a properly cured adhesive layer even when the coating film of the adhesive composition is thick. Therefore, the configuration in which the adhesive layer 12 is a cured product of the active energy ray-curable adhesive composition is suitable for achieving a thick but sufficiently cured adhesive layer 12.
[0088] Examples of the photopolymerization initiator include benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, and thioxanthone photopolymerization initiators. Examples of the benzoin ether photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-1,2-diphenylethane-1-one. As acetophenone-based photopolymerization initiators, for example, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenyl ketone (α-hydroxycyclohexylphenyl ketone), 4-phenoxydichloroacetophenone, and 4-tert-butyldichloroacetophenone can be cited. As α-ketoalcohol-based photopolymerization initiators, for example, 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one can be cited. As aromatic sulfonyl chloride-based photopolymerization initiators, for example, 2-naphthalenesulfonyl chloride can be cited. As photoactive oxime-based photopolymerization initiators, for example, 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime can be cited. As benzoin-based photopolymerization initiators, for example, benzoin can be cited. As benzyl-based photopolymerization initiators, for example, benzyl can be cited. Examples of benzophenone-based photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, and polyvinylbenzophenone. Examples of ketal-based photopolymerization initiators include benzyl dimethyl ketal. Examples of thioxanthone-based photopolymerization initiators include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone. The content of the photopolymerization initiator in the active energy ray-curable adhesive composition is, for example, 0.01% to 3% by weight.
[0089] As the adhesive composition for forming the adhesive layer 12, a solvent-based adhesive composition or an emulsion-based adhesive composition that already contains an acrylic polymer as an adhesive and can be cured by, for example, heating and drying can be used. The composition may contain other components as required as components of the adhesive layer 12 to be formed. The acrylic polymer in the adhesive composition can be obtained by polymerizing the raw monomer components used to form the acrylic polymer. As polymerization methods, for example, solution polymerization, emulsion polymerization, and bulk polymerization can be cited. When performing solution polymerization, as solvents, for example, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, esters, and ketones can be used. As solvents for aromatic hydrocarbons, for example, toluene and benzene can be cited. As solvents for aliphatic hydrocarbons, for example, n-hexane and n-heptane can be cited. As solvents for alicyclic hydrocarbons, for example, cyclohexane and methylcyclohexane can be cited. As solvents for esters, for example, ethyl acetate and n-butyl acetate can be cited. As solvents for ketones, for example, methyl ethyl ketone and methyl isobutyl ketone can be cited. In solution polymerization, one solvent or two or more solvents can be used.
[0090] When the raw monomer components are polymerized to obtain an acrylic polymer, a polymerization initiator may be used. Depending on the type of polymerization reaction, for example, a photopolymerization initiator or a thermal polymerization initiator may be used. During the polymerization, one polymerization initiator may be used or two or more polymerization initiators may be used.
[0091] As the photopolymerization initiator, for example, the above-mentioned benzoin ether photopolymerization initiator, acetophenone photopolymerization initiator, α-ketol photopolymerization initiator, aromatic sulfonyl chloride photopolymerization initiator, photoactive oxime photopolymerization initiator, benzoin photopolymerization initiator, benzyl photopolymerization initiator, benzophenone photopolymerization initiator, ketal photopolymerization initiator and thioxanthone photopolymerization initiator can be listed. The amount of the photopolymerization initiator used is, for example, 0.01 to 3 parts by weight relative to the total amount of the monomer components (100 parts by weight).
[0092] As thermal polymerization initiators, for example, azo polymerization initiators, peroxide polymerization initiators, and redox polymerization initiators can be cited. As azo polymerization initiators, for example, 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, and 4,4'-azobis(4-cyanovaleric acid) can be cited. As peroxide polymerization initiators, for example, benzoyl peroxide and tert-butyl peroxymaleate can be cited. The amount of thermal polymerization initiator used is, for example, 0.05 to 0.3 parts by weight relative to the total amount of monomer components (100 parts by weight).
[0093] When the polymerization for obtaining the above-mentioned acrylic polymer is carried out, a chain transfer agent can be used to adjust the molecular weight of the acrylic polymer. As a chain transfer agent, for example, α-thioglycerol, 2-mercaptoethanol, 2,3-dimercapto-1-propanol, octyl mercaptan, tert-nonyl mercaptan, dodecyl mercaptan (lauryl mercaptan), tert-dodecyl mercaptan, glycidyl mercaptan, thioglycolic acid, methyl thioglycolate, ethyl thioglycolate, propyl thioglycolate, butyl thioglycolate, tert-butyl thioglycolate, 2-ethylhexyl thioglycolate, octyl thioglycolate, isooctyl thioglycolate, decyl thioglycolate and dodecyl thioglycolate can be listed. As a chain transfer agent, one chain transfer agent can be used, or two or more chain transfer agents can be used. In the present embodiment, α-thioglycerol is preferably used as a chain transfer agent. The amount of the chain transfer agent used is, for example, 0.01 to 0.5 parts by weight relative to the total amount of the monomer components (100 parts by weight) used to obtain the acrylic polymer.
[0094] When the adhesive composition for forming the adhesive layer 12, such as an active energy ray-curable adhesive composition, a solvent-based adhesive composition, an emulsion-based adhesive composition, etc., contains the above-mentioned acrylic oligomer, the oligomer can be obtained by polymerizing the raw monomer components of a prescribed composition. As the polymerization method, for example, solution polymerization, emulsion polymerization and bulk polymerization can be listed. As the solvent used for solution polymerization, the above-mentioned substances that can be used as solvents in solution polymerization for obtaining acrylic polymers can be listed. In the solution polymerization, one solvent can be used, or two or more solvents can be used. In addition, when the raw monomer components are polymerized to obtain the above-mentioned oligomer, a polymerization initiator can be used. As the polymerization initiator, the above-mentioned photopolymerization initiator or thermal polymerization initiator that can be used as a polymerization initiator in polymerization for obtaining acrylic polymers can be listed. During polymerization, one polymerization initiator can be used, or two or more polymerization initiators can be used.
[0095] For example, the substrate 11 of the surface protection film X manufactured as described above is a polyester substrate as described above. Such a configuration is suitable for the surface protection film substrate and the surface protection film X to enjoy various properties that polyester substrates tend to exhibit, such as heat resistance, transparency, and dimensional stability.
[0096] In addition, the substrate 11 of the surface protection film X is a uniaxially stretched polyester substrate in the width direction as described above. The thickness of the substrate 11 is 75 μm or more, preferably 80 μm or more, as described above. The thickness of the substrate 11 is preferably 150 μm or less, preferably 125 μm or less, as described above. The tear strength of the surface protection film, such as the Elmendorf tear strength, is strongly controlled by the mechanical properties of the substrate, and these configurations are suitable for realizing the above configuration in the surface protection film X in which the Elmendorf tear strength in the width direction of the substrate is 0.5 N or less and the Elmendorf tear strength in the length direction of the substrate is 1 N or more.
[0097] In addition, the Elmendorf tear strength in the substrate width direction of the surface protection film X is 0.5N or less, preferably 0.45N or less, more preferably 0.4N or less, and more preferably 0.3N or less, as described above. At the same time, the Elmendorf tear strength in the substrate length direction of the surface protection film X is 1N or more, preferably 1.1N or more, more preferably 1.3N or more, and more preferably 1.5N or more, as described above. These structures are suitable for achieving good hand tearing properties in the substrate width direction in the surface protection film X, where the Elmendorf tear strength is relatively intentionally low to 0.5N or less. In addition, the structure in which the Elmendorf tear strength in the substrate length direction is more than twice that in the substrate width direction is suitable for improving the directivity of tearing in the substrate width direction in the surface protection film X. Therefore, this structure is suitable for causing the peeling force to act on the substrate length direction of the surface protection film X when the surface protection film X is in a state of being attached to the adherend, so that the surface protection film X is appropriately peeled off from the adherend without cracking. Specifically, it is suitable for applying a peeling force to the substrate length direction of the surface protective film X during an operation (reprocessing operation) of first peeling off the surface protective film X and then re-bonding the surface protective film X to the adherend, so that the surface protective film X can be properly peeled off from the adherend without cracking. A surface protective film that is easily torn not only in the substrate width direction but also in the substrate length direction tends to be easy to crack when peeled off during the reprocessing operation and is difficult to be properly peeled off from the adherend. A cracked surface protective film cannot be used for re-bonding. In contrast, the surface protective film X has an Elmendorf tear strength in the substrate length direction that is sufficiently large compared to the Elmendorf tear strength in the substrate width direction that is suitable for achieving good hand-tearability along the substrate width direction, and is therefore suitable for being properly peeled off from the adherend without cracking during the reprocessing operation.
[0098] As described above, the surface protection film X is suitable for achieving good hand-tearability and high reworkability while having a polyester-based substrate.
[0099] As described above, the in-plane phase difference of the substrate 11 of the surface protection film X is preferably 1500nm or more, more preferably 3000nm or more, and more preferably 6000nm or more. Such a configuration is suitable for suppressing the so-called black screen phenomenon when the display screen is visually recognized through a lens with a polarization function such as polarized sunglasses when the surface protection film X is attached to the surface of the transparent cover plate as the frontmost component of the display screen of the liquid crystal display device. In addition, the greater the in-plane phase difference of the substrate 11, the more the so-called rainbow spot phenomenon (rainbow mura) tends to be suppressed when the display screen is visually recognized through a lens with a polarization function such as polarized sunglasses when the surface protection film X is attached to the surface of the transparent cover plate as the frontmost component of the display screen of the liquid crystal display device.
[0100] Example
[0101] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to these Examples.
[0102] [Production Example of Acrylic Oligomer]
[0103] In a reaction vessel, a mixture containing 60 parts by weight of tetrahydrodicyclopentadienyl methacrylate (DCPMA), 40 parts by weight of methyl methacrylate (MMA), 3.5 parts by weight of α-thioglycerol as a chain transfer agent, and 100 parts by weight of toluene as a polymerization solvent was stirred at 70°C in a nitrogen atmosphere for 1 hour. Next, 0.2 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was added to the mixture in the reaction vessel to prepare a reaction solution, and the reaction was carried out at 70°C for 2 hours. Next, the reaction was carried out at 80°C for 2 hours. Then, the reaction solution in the reaction vessel was placed in an atmosphere at a temperature of 130°C, and toluene, chain transfer agents, and unreacted monomers were dried and removed from the reaction solution. Thus, a solid acrylic oligomer was obtained. The weight average molecular weight (Mw) of the acrylic oligomer is 5.1×10 3 .
[0104] [Preparation Example of Acrylic PSA Composition C1]
[0105] 0.035 parts by weight of a first photopolymerization initiator (trade name "Irgacure 651", manufactured by BASF) and 0.035 parts by weight of a second photopolymerization initiator (trade name "Irgacure 184", manufactured by BASF) were added to a monomer mixture containing 78 parts by weight of 2-ethylhexyl acrylate (2EHA), 18 parts by weight of N-vinyl-2-pyrrolidone (NVP) and 4 parts by weight of 2-hydroxyethyl acrylate (HEA). The mixture was then irradiated with ultraviolet light using an ultraviolet irradiation device while measuring the viscosity of the mixture using a viscosity measuring device until the viscosity of the mixture reached about 20. . In the viscosity measurement, the rotor rotation speed of the device was set to 10 rpm, and the measurement temperature was set to 30°C. Thus, a prepolymer composition (containing monomer components that have not undergone a polymerization reaction) which is a partial polymer formed by polymerization of a part of the monomer components in the mixture was obtained. Then, 100 parts by weight of the prepolymer composition, 11.8 parts by weight of the above-mentioned acrylic oligomer, 17.6 parts by weight of 2-hydroxyethyl acrylate (HEA), 0.294 parts by weight of 1,6-hexanediol diacrylate (HDDA) and 0.353 parts by weight of a silane coupling agent (trade name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed to obtain an acrylic adhesive composition (acrylic adhesive composition C1).
[0106] [Preparation Example of Acrylic PSA Composition C2]
[0107] In a flask (reaction vessel) equipped with a reflux condenser, a nitrogen inlet tube, a stirrer, and a thermometer, a mixture containing 100 parts by weight of 2-ethylhexyl acrylate (2EHA), 4 parts by weight of 2-hydroxyethyl acrylate (HEA), 0.2 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator, and 205 parts by weight of ethyl acetate as a polymerization solvent was reacted at 63° C. for 4 hours while gently stirring under a nitrogen atmosphere. Thus, a solution containing an acrylic polymer at a concentration of about 35% by weight (acrylic polymer solution) was obtained. Then, the acrylic polymer solution was diluted with ethyl acetate so that the acrylic polymer concentration became 29% by weight, and then 4 parts by weight of trimethylolpropane / toluene diisocyanate adduct (trade name "Coronate L", manufactured by Nippon Polyurethane Industry Co., Ltd.), 0.02 parts by weight of dioctyltin dilaurate (trade name "EMBILIZER OL-1", manufactured by Tokyo Fine Chemicals Co., Ltd.) as a tin-containing catalyst, and 3 parts by weight of acetylacetone as a crosslinking retarder were added to the acrylic polymer solution with respect to 100 parts by weight of the acrylic polymer, and mixed at 25° C. for about 1 minute. Thus, a solvent-based acrylic adhesive composition (acrylic adhesive composition C2) was obtained.
[0108] [Example 1]
[0109] The above-mentioned acrylic adhesive composition C1 is applied to the film (film F1) obtained by applying corona treatment to both sides of a first polyethylene terephthalate film (trade name "COSMOSHINE SRF" with an in-plane phase difference of 8400, manufactured by Toyobo Co., Ltd.) with a thickness of 80 μm, thereby forming an adhesive composition layer. Next, a polyethylene terephthalate (PET)-based release liner (thickness 125 μm, manufactured by Nitto Denko Corporation) is stacked on the adhesive composition layer to cover the adhesive composition layer and block oxygen. In this way, a laminate having a laminated structure of [release liner / adhesive composition layer / film F1] is obtained. Next, a black light lamp (manufactured by Toshiba Corporation) is used to irradiate the laminate from the release liner side for 300 seconds with an illumination of 3mW / cm 2 The adhesive composition layer of the laminate is thereby cured to form an adhesive layer. The thickness of the adhesive layer is 100 μm. A surface protective film of Example 1 having a laminated structure of [peel liner / adhesive layer (thickness 100 μm) / film F1 (thickness 80 μm) as a substrate] was prepared in the manner described above.
[0110] [Example 2]
[0111] The above-mentioned acrylic adhesive composition C2 is applied to the film (film F2) obtained by applying corona treatment to both sides of the second polyethylene terephthalate film having a thickness of 80 μm, thereby forming an adhesive composition layer. The second polyethylene terephthalate film is a film manufactured by Toyobo Co., Ltd., in which the easy-adhesive treatment layer of "COSMOSHINE SRF" as the first polyethylene terephthalate film is replaced with an easy-adhesive treatment layer for hard coating purposes. Then, the adhesive composition layer is heated at 130°C for 60 seconds to dry and cure it, thereby forming an adhesive layer on the film F2. The thickness of the adhesive layer is 21 μm. Then, a PET-type release liner (thickness 25 μm, manufactured by Nitto Denko Corporation) is attached to the surface of the adhesive layer. The surface protective film of Example 2 having a laminated structure of [release liner / adhesive layer (thickness 21 μm) / film F2 (thickness 80 μm) as a substrate] was prepared in the manner described above.
[0112] [Comparative Example 1]
[0113] The surface protection film of Comparative Example 1 was prepared in the same manner as in Example 1 except that a third polyethylene terephthalate film (trade name “XD500P”, in-plane retardation 3000, manufactured by Toray Industries, Inc.) having a thickness of 75 μm and subjected to corona treatment on both sides (film F3) was used as the substrate of the surface protection film instead of film F1.
[0114] [Comparative Example 2]
[0115] A surface protection film of Comparative Example 2 was produced in the same manner as in Example 2 except that the film F3 was used instead of the film F2 as the substrate of the surface protection film.
[0116] <Elmendorf tear strength>
[0117] For each sample piece (60 mm × 75 mm) cut out from the surface protection film of the embodiment and the comparative example, an Elmendorf tear strength measuring device (trade name "Elmendorf tear tester", manufactured by Tester Industry Co., Ltd.) was used to measure the Elmendorf tear strength (N) in the width direction (TD) of the tape substrate and the Elmendorf tear strength (N) in the length direction (MD) of the tape substrate. The measurement was carried out in accordance with JIS K 7128-2. In the sample piece to be measured, a cut with a length of 20 mm extending from its end in the measurement direction (TD or MD) was pre-set. In this measurement, the resistance to the tear load applied to the sample piece by the device in a manner that further extends the cut is measured. In addition, the maximum measurement value of the above-mentioned device used in the measurement is 1N. The results of the measurement are shown in Table 1.
[0118] <Hand-tearability>
[0119] For each surface protective film of the embodiment and the comparative example, the hand-tearability in the width direction of the substrate was examined. Specifically, for the surface protective film from which the release liner was peeled off, the tearing caused by manual operation along the width direction of the substrate was tested. In the manual operation inspection, the situation that can be easily torn is evaluated as good hand-tearability (○), and the situation that cannot be torn is evaluated as poor hand-tearability (×). The results are shown in Table 1.
[0120] <Haze>
[0121] The haze (%) of each surface protective film of the examples and comparative examples was measured using a haze meter HM-150 (manufactured by Murakami Color Research Laboratory Co., Ltd.) according to the method specified in JIS K 7136. The measurement was performed on the surface protective film in a state where the release liner was peeled off and attached to a slide glass (trade name "Slide glass S1112", thickness 1.0 mm to 1.2 mm, manufactured by Matsunami Glass Industries Co., Ltd.). The results are shown in Table 1.
[0122] [evaluate]
[0123] The surface protection films of Examples 1 and 2 having the configuration of the present invention both achieved good hand-tearability. In contrast, the surface protection films of Comparative Examples 1 and 2 both could not be torn by hand in the substrate width direction and did not achieve good hand-tearability.
[0124]
Claims
1. A surface protection film, wherein: The surface protection film has a laminated structure including a transparent substrate and an adhesive layer. The transparent substrate is a uniaxially stretched polyester substrate in the width direction of the substrate and has a thickness of 75 μm or more. The adhesive layer is an acrylic adhesive layer containing 50% by weight or more of monomer units derived from an alkyl (meth)acrylate having a linear or branched alkyl group in an acrylic polymer. The Elmendorf tear strength of the surface protection film in the width direction of the substrate is 0.5N or less and the Elmendorf tear strength of the surface protection film in the length direction of the substrate is 1N or more, The surface protection film is in a form of being wound into a roll with the longitudinal direction of the substrate as the longitudinal direction.
2. The surface protection film according to claim 1, wherein The pressure-sensitive adhesive layer is a pressure-sensitive adhesive layer containing an acrylic pressure-sensitive adhesive in which the ratio of monomer units derived from a hydroxyl group-containing monomer in an acrylic polymer is 1% by weight or more and 20% by weight or less.
3. The surface protection film according to claim 1 or 2, wherein: The pressure-sensitive adhesive layer is a pressure-sensitive adhesive layer containing an acrylic pressure-sensitive adhesive in which the ratio of monomer units derived from a polyfunctional (meth)acrylate in an acrylic polymer is 0.01% by weight to 1% by weight.
4. The surface protection film according to claim 1 or 2, wherein: The adhesive layer includes a silane coupling agent, and the content of the silane coupling agent is 0.01 parts by weight to 1 part by weight relative to 100 parts by weight of the acrylic polymer.
5. The surface protection film according to claim 1 or 2, wherein: The adhesive layer has a thickness of 5 μm or more.
6. The surface protection film according to claim 1 or 2, wherein: The surface protection film has a haze of 3% or less.
